Islamic Education Management in Preparing the Demographic Bonus in Indonesia in 2045 - Sedya Santosa; Barirohmah Barirohmah (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Indonesia is a country that has the fourth largest population in the world. Indonesia is predicted to be one of the countries in the world that will experience the demographic bonus phenomenon in 2045. The demographic bonus in Indonesia in 2045 will be an opportunity if it can take advantage of it and will be a disaster if it cannot take advantage of it. Efforts to take advantage of the demographic bonus opportunity in Indonesia in 2045 are to equip or prepare the golden generation with education. The Muslim population is predominantly Muslim, so Islamic education management has an important role in preparing education for the golden generation who will become the next generation of the Indonesian nation. This study uses the Systematic Literature Review method. Systematic and interpreting methods are from books, scientific journals, blog posts, documents, and articles obtained by existing research questions following the themes and phenomena of interest, relevant research. The Literature Review data and information are used in research that aims to identify, review, and evaluate online media. The results of research using the Literature Review method revealed that Islamic education based on the Qur'an and Sunnah would be able to create a superior generation. This generation has identity/character and is useful for society.